2015
DOI: 10.1530/eje-15-0048
|View full text |Cite
|
Sign up to set email alerts
|

Changes in circulating IGF1 receptor stimulating activity do not parallel changes in total IGF1 during GH treatment of GH-deficient adults

Abstract: Context: Previously we demonstrated that IGF1 receptor stimulating activity (IGF1RSA) offers advantages in diagnostic evaluation of adult GH deficiency (GHD). It is unknown whether IGF1RSA can be used to monitor GH therapy. Objective: To investigate the value of circulating IGF1RSA for monitoring GH therapy. Design/methods: 106 patients (54 m; 52 f) diagnosed with GHD were included; 22 were GH-naïve, 84 were already on GH treatment and discontinued therapy 4 weeks before baseline values were established. IGF1R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…In addition, IRSA remained below normal in more than 40% of patients in whom total IGF-I had normalized [89]. Interestingly, the increase of the IGF-I/IGFBP3 ratio (which has been suggested to reflect an estimate of bioavailable IGF-I) after 12 months GH treatment was almost similar to the reported increase of IRSA [89].…”
Section: Irsa and Ghdsupporting
confidence: 66%
See 3 more Smart Citations
“…In addition, IRSA remained below normal in more than 40% of patients in whom total IGF-I had normalized [89]. Interestingly, the increase of the IGF-I/IGFBP3 ratio (which has been suggested to reflect an estimate of bioavailable IGF-I) after 12 months GH treatment was almost similar to the reported increase of IRSA [89].…”
Section: Irsa and Ghdsupporting
confidence: 66%
“…After start of GH treatment both IRSA and total IGF-I significantly increased but changes in IRSA did not parallel changes in total IGF-I [89]. After 12 months of GH treatment total IGF-I normalized in 81% of patients, whereas in only 50% of patients the IRSA was in the normal reference range [89]. In addition, IRSA remained below normal in more than 40% of patients in whom total IGF-I had normalized [89].…”
Section: Irsa and Ghdmentioning
confidence: 88%
See 2 more Smart Citations
“…We believe this gives a biologically relevant estimate of the ability of serum IGF-I to activate the IGF-IR, and hence IGF-bioactivity. Indeed, a discrepancy between bioactive and total levels of IGF-I has been reported in both adults (14) and children (15) and it was reported that in adults, bioactive IGF concentrations correlated better with the diagnosis of GH deficiency (GHD) than total IGF-I levels (16).…”
Section: Measurements Of the Concentration Of Total Igf-i By Immunoasmentioning
confidence: 99%